CCR1 as a target for multiple myeloma - Vallet, Sonia; Anderson, Kenneth C. (Expert opinion on therapeutic targets, 2011)
Introduction: By directing cell trafficking, differentiation and growth, chemokines modulate the immune response and are involved in the pathogenesis of autoimmune diseases and cancers, including multiple myeloma (MM). MM, the second most common hematological malignancy in the US, is characterized by disordered plasma cell growth within the bone marrow microenvironment. CCL3 and its receptors, CCR1 in particular, play a central role in the pathogenesis of MM and MM-induced osteolytic bone disease. Areas covered: This review describes the functional role of CCR1 in MM and the preclinical results observed with CCR1 antagonists. CCL3 and CCR1 stimulate tumor growth, both directly and indirectly, via upregulation of cell adhesion and cytokine secretion. In addition, they modulate the osteoclast/osteoblast balance, by inducing osteoclast differentiation and inhibiting osteoblast function. Targeting either ligand or receptor reverses these effects, leading to in vivo tumor burden control and prevention of osteolysis, as confirmed in both murine and humanized mouse models. Expert opinion: These promising data set the stage for clinical trials to assess the effects of CCR1 inhibitors in MM. The success of these studies depends on the development of novel antagonists with improved chemical/physical properties and careful selection of the patient population who may benefit the most from these agents.
Gesehen am 01.12.2022